Genetic characterization of cpti and nptii genes in the hybrids of transgenic and non-transgenic apple (Bangladesh Journal of Botany, 2024)
To investigate the inheritance and expression of exogenous cowpea trypsin inhibitor (CpTI) and neomycin phosphotransferase II (nptII) genes in the progenies of transgenic apples (Malus domestica Borkh.), hybrid (F1) fruits and seeds were obtained using transgenic Gala and non-transgenic Fuji for cross and reciprocal cross experiments. Transgenic apple hybrid F1 plants were obtained using the established apple embryo culture system. The law of segregation of nptII in the hybrid progeny was studied through successive selections under high-level kanamycin pressure. The genetic linkage between CpTI and nptII was tested by      PCR      analysis. The effects of exogenous genes on transgenic apple fruits were       measured by nptII enzyme activity, fruit weight, fruit shape index, fruit hardness, soluble solids content, acid content, and other related indicators in the transgenic Gala fruit. The      kanamycin resistance test in F1 plantlets 1:1 Mendelian ratio       of kanamycin resistance to non-resistance      . Thus, the nptII marker gene, a dominant heterozygous gene, passed onto the progenies through sexual hybridization.      PCR analysis also showed that CpTI was closely linked to nptII     . The activity of nptII enzyme was detected in most transgenic apples, but the intensity of nptII enzyme activity in different fruits was different.. Transgenic Gala fruit and the control fruit were oblate or nearly round, with the fruit shape index ranging between 0.83 and 0.90. Acid content of a transgenic fruit was not significantly different compared to the control. Fruit hardness and soluble solids content were significantly lower compared to the control. The results provide a reference for further studies on the genetic characteristics of transgenic apples and the utilization of transgenic products.Bangladesh J. Bot. 53(4): 1043-1053, 2024 (December)